Development of Nano-Satellite, AEROSAT for Space Education - Ismail, Norisza Dalila; Hambali, Mohammad Najmi; Anak Eric Daniel, Shanen Jane; Md Zahirul Islam, Nur Eliana (Multidisciplinary Applied Research and Innovation, 2021)
An AEROSAT is a simulation of a real satellite, integrated within the volume and shaped of a frustum structure. The challenge is to fit all the major subsystems found in a satellite, such as power, sensors and a communication system, into this minimal volume. The AEROSAT is then sent to an altitude of a few hundred metres by a drone and its mission begins: to carry out a scientific experiment and achieve a safe landing. AEROSAT offers a unique opportunity for students to have a first practical experience of a real space project. They are responsible for all aspects: selecting the mission objectives, designing the AEROSAT, integrating the components, testing, preparing for launch and then analysing the data. Throughout this process the students: learn by doing, get acquainted with the inquiry-based methodology that is typical of real-life scientific and technical professions and acquire and/or reinforce fundamental Aerodynamics, Physics, and programming curricular concepts.